Compenting vendors in the telecom value chain - Gök, Ünal. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
We consider the competition between two vendors that serve a common telecommunication operator. The two vendors make independent investments on research and development of the same or substitutable innovative technology which strictly increases the demand of the operator if the innovation ever materializes. The operator buys the innovative technology from the vendor that achieves it first and then decides on the extra capacity to build in each period. In the first model, it is assumed that the operator chooses the cheaper vendor to buy the technology from. Whereas in the second model, the operator chooses the more profitable option if both vendors come up with the same technology. For both models, the centralized solution is characterized in which a single decision maker oversees the whole system. This solution acts as a benchmark for the decentralized analysis. In the decentralized setting, the vendors play a simultaneous investment game first and then they offer the operator a contract. The operator's decisions are fully characterized for both models. For the first model we provide negative result via counter-examples for the non-existence of a Nash equilibrium. For the second model, we characterize the conditions under which a unique Nash equilibrium exists. We provide a computational study to gain insight about how innovation plays a role in the vendors' game. Moreover, profit and revenue sharing coordinating contracts are proposed for the telecom value chain. The effect of the contract parameters on profit values is monitored by a numerical illustration.
Keywords: Business logistics .